Consequences of Ca Codoping in YAlO3:Ce Single Crystals. Issue 5 (18th January 2017) - Moretti, Federico; Hovhannesyan, Karine; Derdzyan, Marina; Bizarri, Gregory A.; Bourret, Edith D.; Petrosyan, Ashot G.; Dujardin, Christophe
Abstract: The influence of Ca codoping on the optical absorption, photo‐, radio‐, and thermo‐luminescence properties of YAlO3 :Ce (YAP:Ce) crystals has been studied for four different calcium concentrations ranging from 0 to 500 ppm. Ca codoping results in a partial oxidation of Ce 3+ into Ce 4+, The luminescence time response under pulsed X‐ray excitation of the Ce 3+ /Ce 4+ admixure clearly demonstrates the role of hole migration on both the rise time and the generally observed slow components. From an application point of view, Ca codoping significantly improves the timing performances, but the induced presence of Ce 4+ ions is also the cause of a reduction in scintillation efficiency. Abstract : Taking a shortcut : Ca codoping in YAlO3 :Ce single crystal is able to shorten the scintillation decay time (see Figure), though this is also accompanied by a general reduction of the scintillation efficiency. The lower efficiency is mostly related to reabsorption and energy transfer phenomena involving Ce 3+ and Ce 4+ ions.